CAMBODIAN GRADE-12 STUDENTS’ PERCEPTIONS OF PUBLIC ENGLISH TEXTBOOK AND EXAM PAPERS - Sereyrath Em; Nel Nun (IKIP Siliwangi, 2022)
English is a native language of some countries, a foreign language for many countries, and an international language for the whole world. English textbook is one of the most important learning and teaching materials in learning and teaching this language to succeed. This article aimed to examine students’ perception of their high school English textbook toward high school national exam papers. The article also aimed to examine students’ perceptions of English textbook that they want so that their needs for English, like daily activities and high school exams, are fulfilled. The study employed a qualitative design. 20 students participated in the study. The findings show that the current textbook is out of date. All the students wanted a new textbook providing them with the daily needs of English and the keys to passing their high school exams. A bigger sample size might be used in a future investigation. It is strongly suggested that the impact of English textbook on students' learning achievements be investigated. It is also suggested that teachers' attitudes toward English textbooks be examined. Keywords: Cambodia, English Textbook, Grade-12 Student, High School Exam